2018
DOI: 10.1080/1059924x.2017.1422836
|View full text |Cite
|
Sign up to set email alerts
|

What Happens to the Farm? Australian Farmers’ Experiences after a Serious Farm Injury

Abstract: Farmers who have sustained a serious farm-related injury are an important resource; their experiences and perspectives could assist in the development of educational and transitional support services from recovery back to working at a preinjury level, while ensuring farming production is sustainable during this period. Furthermore, farm safety programs can be enhanced by the engagement of farmers, such as participants in this study as advocates for improved farm safety practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…Our findings around farming-related injuries confirm those from international studies, in terms of the most common mechanisms for injury being agricultural machinery (including vehicles), interaction with livestock and falls. 3,7,8,[17][18][19][20][21][22] Our study has identified some high-risk mechanisms for injury, regardless of whether individuals were undertaking a farming activity or not. In summary, some of the key risks in the Midland region are for:…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Our findings around farming-related injuries confirm those from international studies, in terms of the most common mechanisms for injury being agricultural machinery (including vehicles), interaction with livestock and falls. 3,7,8,[17][18][19][20][21][22] Our study has identified some high-risk mechanisms for injury, regardless of whether individuals were undertaking a farming activity or not. In summary, some of the key risks in the Midland region are for:…”
Section: Discussionmentioning
confidence: 81%
“…1,2 In New Zealand, as elsewhere, farming is recognised as an inherently dangerous occupation, being overrepresented in injury statistics. 3,4 However, farms are usually both a workplace and a home, bringing particular challenges for safety in terms of the physical and social environment of a farm. 3,5 Health and safety improvement in the agricultural sector is a high priority for WorkSafe New Zealand (Worksafe), as the national regulator of health and safety at work, as well as national and regional industry groups.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research suggests that farmers are often willing to share their stories to minimise the risk for others [ 108 ]. Absent from the literature is the exploration into the lived experiences of child farm-related injury.…”
Section: Discussionmentioning
confidence: 99%